الزمكانية وأثرها على التحولات البنيوية للمسكن كمدخل لتحقيق التساوق الاجتماعي - بدر رنا (Latakia University Journal -Engineering Sciences Series, 2016)
تناوبت مخرجات العلاقة التفاعلية بين المسكن كمكان يحتضن الأسرة كساكن، متمثلة أفعالاً اجتماعية مختلفة الاتجاه والأثر. وعلى اعتبار أن الأسرة هي اللبنة الأساسية في بناء المجتمعات، فان مدى استقرارها وتمتعها بالسكينة في مكانها (مسكنها) يسوقها الى تصدير أفعال ايجابية نحو المجتمع مساهمة في بناءه المستدام فيكون تساوقاً اجتماعياً ( تلاؤماً)، والعكس صحيح فيكون عزلة مجتمعية . ولطالما ساهم المجتمع المعرفي بدراسات وأبحاث متعددة ومتنوعة للعلاقة التفاعلية بين الساكن والمسكن ومخرجاتها على فترات زمنية مختلفة، إلا أن هذه الدراسات اتسمت بالخطية بعيداً عن التشابكية في كثير من الأحيان من جهة ، ولم تستخلص الايجابيات الزمكانية كموجهات يمكن البناء عليها من جهة أخرى لتفعيل هذه العلاقة ايجاباً وتحقيق التساوق والتلاؤم الأسري والمجتمعي. وعليه تمحور البحث حول الاهتمام بالعلاقة بين الساكن والمسكن باسلوب تشابكي مستهدفة قوامها النظري باسقاطاتها الزمكانية عبر تقييم وتحليل، تَستخلص بموجبه موجهات مسلكية تعتمد على المخرجات الايجابية لتلك العلاقة التفاعلية كنقاط ارتكاز دافعة للتلاؤم فيما بين مكونات تلك العلاقة محققة رافداً للتساوق الاجتماعي، كما تقوم في الوقت نفسه باستيضاح مخرجاتها السلبية بهدف تلافيها والحد منها والتي بوجودها تخلق عزلة مجتمعية. The outputs of the interactional relation between residence as a place contains the family as a resident had alternated ,representing by a social actions which are different in direction and impact. Taking into consideration that family is the first stone in building up of societies ,the extent of its stability and having quietness inside its place(residence)will drive it to export a positive actions towards the society contributing in its sustaining building and resulting a social symmetry (suitability) For a long time The knowledge society had contributed in various and numerous studies about the interactional relation between residence and resident and its outputs along different temporal periods ,but for one direction in many times these studies were linear away from interlocking ,and did not extract the spacetime positives as a guidelines which enable to be built up on from another direction to activate that relation positively and achieving the social and family symmetry and suitability Upon to that the research concentrates on taking care about the interlocking relation between resident and residence aiming for its theoretical structure with its spacetime implementations through evaluation and analysis ,which in turn work towards extracting a route guidelines depending on the positive outputs of that interactional relation as a pushing fulcrum points towards suitability among the components of that relation achieving a branch of the social symmetry .working at the same time on declaring its negative outputs for avoiding and stopping it according to its role in creating a sociable isolation